(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To compare the effectiveness of improving pain level, range of motion, and Neck Disability Index (NDI) of neck and shoulder joint movement exercises taught University of Medicine and Pharmacy at Ho Chi Minh City and cervical spine joint exercise according to the Ministry of Health’s rehabilitation protocol on patients with cervical spondylosis. Research methods: This is a non-blind clinical trial with a control group, comparing pre- and post-treatment outcomes over a 14-day period from April to August 2024. The study involved 60 patients aged 18 to 60 years, diagnosed with cervical spondylosis, and divided into two groups at the Rehabilitation Hospital for Rehabilitation and Occupational Diseases. The intervention group received medication combined with 3 sessions of neck and 3 sessions of shoulder joint movement exercises, while the control group received medication with self-guided cervical spine exercises according to the Ministry of Health’s protocol. The study used standardized goniometers. Results: The intervention group, showed significant reductions in neck and shoulder VAS scores, improvements in cervical spine and shoulder range-of-motion, as well as daily functional improvements based on NDI after 14 days (p<0.05). The intervention group performed better than the control group. Conclusion: The intervention group demonstrated increased joint range-of-motion, reduced neck and shoulder pain, and improved daily functional activities, showing better overall treatment outcomes compared to the control group.